Влияние канала реакции на изомерное отношение при получении 184m, gRe - Асатрян, Р. В. (Հայաստանի ԳԱԱ)
The influence of reaction channel on the Isomeric Cross-section Ratio (ICR) of the production of 184m,gRe was investigated. The excitation functions for the 184m,gRe isomeric pair produced through the 184W(p,n), 186W(p,3n), 184W(d,2n), 186W(d,4n), 181Ta(α,n) and 185Re(γ,n) reactions were calculated by different models of TALYS 1.9 and EMPIRE 3.2 codes. The ICR calculated for the above mentioned isomeric pair through various reaction channels (proton, deuteron, alpha and gamma induced reactions) was determined for incident energy ranges from threshold up to 50 MeV. The comparisons of theoretical calculations with the available experimental data for the reactions were done.
Keywords: Nuclear Physics